2021
DOI: 10.3390/su13179981
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the Implications of Dispersing Teams and Teleworking in an Agile UK Construction Sector

Abstract: A scientometric analysis of extant literature is conducted to elucidate upon the practicality of teleworking throughout industry as a prelude to prescribing a bespoke conceptual adoption model that embeds innovative digital technologies to facilitate teleworking for construction professionals. The model is premised upon the Royal Institute of British Architects (RIBA) work stages and illustrates how technologies are being used at each incremental stage. An interpretivist philosophy and inductive reasoning were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 87 publications
(149 reference statements)
1
10
0
1
Order By: Relevance
“…This philosophical stance was corroborated by an interpretivist review of the literature (cf. Edwards et al, 1998;Burton et al, 2021;, which revealed that a quantitative research strategy was commonly used in previous similar studies (cf. Owusu-Manu et al, 2019;Spellacy et al, 2020;Owusu-Manu et al, 2021).…”
Section: Research Frameworkmentioning
confidence: 98%
“…This philosophical stance was corroborated by an interpretivist review of the literature (cf. Edwards et al, 1998;Burton et al, 2021;, which revealed that a quantitative research strategy was commonly used in previous similar studies (cf. Owusu-Manu et al, 2019;Spellacy et al, 2020;Owusu-Manu et al, 2021).…”
Section: Research Frameworkmentioning
confidence: 98%
“…Identifying word frequencies and word associations are just two of the many text analytics that Voyant Tools produces from a series of user-inputted text sources [17]. Voyant Tools has been successful used in a wide range of academic publications and in the built environment disciplines [18,19].…”
Section: Scientometric and Text Analysismentioning
confidence: 99%
“…The term teleworking (or telecommuting) was first coined by Jack Nilles (an engineer in the National Aeronautics and Space Administration (NASA)) in the 1970s, which entails utilizing data, information, and technology-related interfaces to support tasks and activities -undertaken away from the traditional office-based workplace (Allen et al, 2015;Burton et al, 2021). Since then, the term utilized frequently has been telecommuting, alternatively also known as 'remote working' (Allen et al, 2015;Burton et al 2021;Daniels et al, 2001).…”
Section: Literature Reviewmentioning
confidence: 99%